Lurasidone for major depressive disorder with mixed features and irritability: a post-hoc analysis. (16th March 2017) - Swann, Alan C.; Fava, Maurizio; Tsai, Joyce; Mao, Yongcai; Pikalov, Andrei; Loebel, Antony
Abstract : Objective: The aim of this post-hoc analysis was to evaluate the efficacy of lurasidone in treating major depressive disorder (MDD) with mixed features including irritability. Methods: The data in this analysis were derived from a study of patients meeting DSM–IV–TR criteria for unipolar MDD, with a Montgomery–Åsberg Depression Rating Scale (MADRS) total score ≥26, presenting with two or three protocol-defined manic symptoms, and who were randomized to 6 weeks of double-blind treatment with either lurasidone 20–60 mg/d ( n =109) or placebo ( n =100). We defined "irritability" as a score ≥2 on both the Young Mania Rating Scale (YMRS) irritability item (#5) and the disruptive-aggressive item (#9). Endpoint change in the MADRS and YMRS items 5 and 9 were analyzed using a mixed model for repeated measures for patients with and without irritability. Results: Some 20.7% of patients met the criteria for irritability. Treatment with lurasidone was associated with a significant week 6 change vs. placebo in MADRS score in both patients with (–22.6 vs. –9.5, p <0.0001, effect size [ ES ]=1.4) and without (–19.9 vs. –13.8, p <0.0001, ES =0.7) irritability. In patients with irritable features, treatment with lurasidone was associated with significant week 6 changes vs. placebo in both the YMRS irritability item (–1.4 vs. –0.3, p =0.0012, ES =1.0) and the YMRS disruptive-aggressive item (–1.0 vs. –0.3, p =0.0002, ES =1.2). Conclusions: In our post-hoc analysis of a randomized, placebo-controlled, 6-week trial, treatment with lurasidone significantly improved depressive symptoms in MDD patients with mixed features including irritability. In addition, irritability symptoms significantly improved in patients treated with lurasidone.